Müllerian papilloma: two case reports of malignant transformation and literature review - Tao, Sirong; Zhang, Yan; Wang, Wei; He, Ying; Jiang, Lili (Frontiers in Oncology, 2025)
BackgroundMüllerian papilloma is a rare benign genital tract tumor, and its malignant transformation is extremely rare. Due to its complex and diverse pathological morphological manifestations, it is prone to misdiagnosis.MethodsWe reported the malignant transformation of Müllerian papilloma into endometrioid carcinoma in two young girls, along with their pathological results. For the first time, we combined next-generation sequencing (NGS) technology to explore the molecular characteristics.ResultsThe two cases of malignant transformation into endometrioid adenocarcinoma exhibited similar pathological morphology and immunohistochemical (IHC) markers. Morphologically, they presented complex and diverse features. The benign areas showed a mild papillary structure, while the malignant areas displayed complex papillary branches, cribriform patterns, and solid structures, accompanied by hemorrhage, necrosis, and interstitial inflammatory cell infiltration. In terms of IHC, CK7 and EMA were either focally positive or diffusely positive; Vimentin, P16, and SALL-4 were negatively expressed; P53 showed wild-type expression; the ki67 proliferation index was 35-45%. Subsequent sequencing revealed a low tumor mutation burden and stable microsatellites. However, three novel fusion genes were identified.ConclusionThe malignant transformation of Müllerian papilloma is extremely rare, with complex and diverse morphological manifestations. High vigilance is required during diagnosis to avoid confusion with sarcomas. This tumor has a low tumor mutation burden and stable microsatellites, and the exact mechanism of malignant transformation requires further investigation.